Spinel-type lithium manganese oxide, its manufacturing method and its use

JP7631822B2Active Publication Date: 2025-02-19TOSOH CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021006162
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-19
Publication Date
2025-02-19
Estimated Expiration
2041-01-19

AI Technical Summary

Benefits of technology

【0009】 本発明のスピネル型マンガン酸リチウムは、これをリチウム二次電池用正極材料に使用する場合、従来に比べて高温における充放電特性、特にカーボン対極充放電特性に優れるリチウム二次電池の提供が可能になる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631822000001
    Figure 0007631822000001
  • Figure 0007631822000002
    Figure 0007631822000002
Patent Text Reader

Abstract

To provide a spinel type lithium manganate excellent in charge / discharge characteristics at a high temperature and a lithium secondary battery excellent in charge / discharge characteristics at a high temperature.SOLUTION: A spinel type lithium manganate contains a phosphate and is represented by chemical formula Li1+XMn2-X-Y-ZMgYMZO4 (In the formula, M is at least one element selected from Al, Ca, Ti, V, Cr, Co, and Ni, and 0.02≤X≤0.10, 0.05≤Y≤0.30, 0≤Z≤0.30), in which the Hausner ratio represented by the ratio of tap density to bulk density is 1.85 or less. A method for producing the spinel type lithium manganate and the use thereof are also provided.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a spinel-type lithium manganese oxide, a manufacturing method thereof, and uses thereof, and more particularly to a spinel-type lithium manganese oxide having a phosphate attached to its surface, a manufacturing method thereof, and a lithium secondary battery using the same in an electrode. [Background technology]

[0002] Lithium secondary batteries have a higher energy density than other storage batteries, and are therefore widely used as storage batteries for mobile devices. Recently, research has been conducted to further improve their performance, such as for use in large-scale stationary and automotive applications that require large capacity and high output.

[0003] The positive electrode material of current lithium secondary batteries is mainly cobalt-based material (LiCoO2) for small consumer batteries such as mobile phones, and nickel-based material (LiNi 0.8 Co 0.15 Al 0.05 O2) and nickel-cobalt-manganese ternary materials (LiNi 0.5 Co 0.2 Mn 0.3 O2, etc.) are mainly used. However, cobalt and nickel raw materials are scarce and expensive, and the output characteristics are not very high.

[0004] On the other hand, spinel-type lithium manganese oxide, a manganese-based material, is one of the materials suitable for large batteries and applications requiring high output, because the raw material manganese is abundant and inexpensive, and it also has excellent output characteristics and safety.

[0005] However, spinel-type lithium manganese oxide has a problem in high-temperature stability, that is, in charge / discharge characteristics at high temperatures, particularly in the charge / discharge characteristics and storage characteristics of the carbon counter electrode, and a solution to this problem has been desired. For example, Patent Document 1 and Patent Document 2 both propose spinel-type lithium manganese oxide containing phosphate, but there is still room for improvement in the charge / discharge characteristics at high temperatures, particularly in the charge / discharge characteristics of the carbon counter electrode. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 5556983 [Patent Document 2] JP 2017-31006 A Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a spinel-type lithium manganese oxide having excellent charge-discharge characteristics at high temperatures, particularly excellent carbon counter electrode charge-discharge characteristics, and further to provide a lithium secondary battery using the spinel-type lithium manganese oxide in the positive electrode. [Means for solving the problem]

[0008] The present inventors have conducted extensive research into spinel-type lithium manganese oxide. As a result, they have found that the present invention, which is summarized below, can achieve the above-mentioned object. That is, the present invention relates to a lithium manganese oxide having a phosphate and a chemical formula of Li 1+X Mn 2-X-Y-Z Mg Y M ZThe present invention relates to a spinel-type lithium manganese oxide having the following formula: O4 (wherein M is at least one element selected from Al, Ca, Ti, V, Cr, Co and Ni, and 0.02≦X≦0.10, 0.05≦Y≦0.30, and 0≦Z≦0.30), characterized in that the Hausner ratio, which is expressed as the ratio of tap density to bulk density, is 1.85 or less, and a production method and uses thereof. Effect of the Invention

[0009] When the spinel-type lithium manganese oxide of the present invention is used as a positive electrode material for a lithium secondary battery, it becomes possible to provide a lithium secondary battery having superior charge / discharge characteristics at high temperatures, particularly superior carbon counter electrode charge / discharge characteristics, as compared with conventional batteries. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in detail below.

[0011] The spinel-type lithium manganese oxide of the present invention has the chemical formula Li 1+X Mn 2-X-Y-Z Mg Y M Z O4 (wherein M is at least one element selected from Al, Ca, Ti, V, Cr, Co and Ni, and 0.02≦X≦0.10, 0.05≦Y≦0.30, and 0≦Z≦0.30).

[0012] In the chemical formula, M may be at least one element selected from the group consisting of Al, Ca, Ti, V, Cr, Co and Ni.

[0013] In the chemical formula, if the value of X is less than 0.02, the capacity is likely to decrease during charging and discharging at high temperatures, and if it exceeds 0.10, sufficient charging and discharging capacity is not obtained. If the value of Y is less than 0.05, the capacity is likely to decrease during charging and discharging at high temperatures, and if it exceeds 0.30, sufficient charging and discharging capacity is not obtained. If the value of Z is more than 0.30, sufficient charging and discharging capacity is not obtained. X, Y, and Z of the spinel-type lithium manganate can be determined by composition analysis. Examples of the method include inductively coupled plasma emission spectrometry and atomic absorption spectrometry.

[0014] The spinel-type lithium manganate of the present invention has a Hausner ratio of 1.85 or less. The Hausner ratio of 1.85 or less increases the fluidity of the powder, and when used as a positive electrode active material of a lithium secondary battery, the uniformity with a conductive assistant or binder increases, improving the charge / discharge characteristics, especially the carbon counter electrode charge / discharge characteristics. If the Hausner ratio exceeds 1.85, the uniformity when mixed with a conductive assistant or binder decreases, and the charge / discharge characteristics decrease, which is not preferable. The Hausner ratio is preferably 1.80 or less, more preferably 1.70 or less, and even more preferably 1.60 or less. Here, the Hausner ratio refers to the ratio of tap density to bulk density.

[0015] When the spinel-type lithium manganese oxide of the present invention is used as a positive electrode active material for a lithium secondary battery, a reaction of capturing a small amount of hydrogen fluoride contained in the electrolyte of the lithium secondary battery with a phosphate proceeds quickly, and as a result, manganese elution caused by the reaction between hydrogen fluoride and the spinel-type lithium manganese oxide is suppressed, and it becomes possible to suppress a capacity decrease during charging and discharging at high temperatures, so that the phosphorus / manganese molar ratio is preferably 0.0015 or more and 0.1 or less. The phosphorus / manganese molar ratio is preferably 0.002 or more and 0.05 or less, and more preferably 0.004 or more and 0.01 or less.

[0016] The spinel-type lithium manganese oxide of the present invention contains a phosphate. The phosphate contained in the spinel-type lithium manganese oxide is, for example, a lithium phosphate such as Li3PO4 or LiPO3, or Na3PO 4、 Examples of the phosphate include sodium phosphates such as NaH2PO4 and Na2HPO4, and potassium phosphates such as K3PO4, KH2PO4 and K2HPO4. Li3PO4 and LiPO3 are preferred, and Li3PO4 is more preferred. By including the above phosphate in the spinel-type lithium manganate, it becomes possible to obtain excellent charge-discharge characteristics at high temperatures when used as a positive electrode active material for a lithium secondary battery. The nature of the phosphate to be included is not particularly limited, and examples include crystalline, crystalline and porous, crystalline and dense, amorphous, amorphous and porous, and amorphous and dense, but is not limited thereto.

[0017] The spinel-type lithium manganese oxide of the present invention, when used as a positive electrode active material for a lithium secondary battery, can provide excellent charge / discharge characteristics at high temperatures and can also provide excellent output characteristics. Therefore, it is preferable that the spinel-type lithium manganese oxide has a BET specific surface area of ​​0.2 m or less. 2 / g or more 1.5m 2 The BET specific surface area is preferably 0.2 m 2 / g or more 1.0m 2 / g or less is preferable, and 0.2m 2 / g or more 0.6m 2 / g or less is more preferable.

[0018] The spinel-type lithium manganese oxide of the present invention, when used as a positive electrode active material for a lithium secondary battery, can provide excellent output characteristics and can improve the packing of the positive electrode mixture, so that the average particle size of the secondary particles is preferably 4 μm or more and 20 μm or less, more preferably 5 μm or more and 15 μm or less, and more preferably 5 μm or more and 10 μm or less.

[0019] When the spinel-type lithium manganate of the present invention is used as a positive electrode active material of a lithium secondary battery, it has high crystallinity, suppresses the elution of manganese, suppresses the crystal structure change accompanying charge and discharge, and obtains excellent charge and discharge characteristics at high temperatures. Therefore, the half-value width of the (400) plane by XRD measurement is preferably 0.005 or more and 0.06 or less, and more preferably 0.005 or more and 0.05 or less. The method for measuring the half-value width is carried out by <Measurement of the half-value width by XRD> in the examples. In order to correct the error of the measuring device, after measuring a standard substance in advance, the half-value width of the standard substance is subtracted from the half-value width of the spinel-type lithium manganate and calculated.

[0020] When the spinel-type lithium manganate of the present invention is used as a positive electrode active material of a lithium secondary battery, it increases the charge and discharge capacity and obtains excellent charge and discharge characteristics at high temperatures. Therefore, the content of SO4 is preferably 0.3 wt% or more and 1.0 wt% or less, and more preferably 0.4 wt% or more and less than 0.7 wt%.

[0021] When the spinel-type lithium manganate of the present invention has high crystallinity and is used as a positive electrode active material of a lithium secondary battery, in order to obtain excellent charge and discharge characteristics at high temperatures, the content of Na is preferably 3,000 wtppm or less, and more preferably 1,000 wtppm or less.

[0022] Next, a method for producing the spinel-type lithium manganate of the present invention will be described.

[0023] The spinel-type lithium manganate of the present invention is obtained by mixing a magnesium-manganese-M element composite raw material (M is at least one element selected from Al, Ca, Ti, V, Cr, Co, and Ni; the same applies hereinafter), a lithium raw material, and a phosphoric acid raw material, and firing at 830 °C or higher and 960 °C or lower in the air or in a high-concentration oxygen atmosphere (including a pure oxygen atmosphere), and then pulverizing.

[0024] The magnesium-manganese-M element composite raw material is not limited in form or state, and by using a composite compound (magnesium-manganese-M element composite raw material) obtained by a coprecipitation method or the like as a raw material, it is possible to obtain spinel-type lithium manganate with better homogeneity of metal elements.

[0025] The magnesium-manganese-M element composite raw material can be produced by mixing an aqueous solution containing a magnesium salt compound, a manganese salt compound and a compound of the M element, and an oxidizing agent under a condition of pH 8.5 to 10.0.

[0026] Examples of the magnesium salt compound include water-soluble magnesium salts such as magnesium sulfate, magnesium hydroxide, and magnesium acetate.

[0027] Examples of the manganese salt compound include water-soluble manganese salts such as manganese sulfate and manganese nitrate.

[0028] Examples of the compound of the M element include water-soluble salts of the M element, such as aluminum sulfate, nickel sulfate, and cobalt sulfate.

[0029] In producing the magnesium-manganese-M element composite raw material, the ratio of magnesium, manganese and M element is preferably adjusted to match the ratio of magnesium:manganese:M element of the desired spinel-type lithium manganate.

[0030] The total concentration (metal concentration) of magnesium, manganese and M element in the aqueous metal salt solution is not limited, but is preferably 1.0 mol / L or more, and more preferably 2.0 mol / L or more, in terms of excellent productivity.

[0031] In order to maintain the reaction conditions at pH 8.5 to 10.0, it is preferable to add and mix an acid or a base as appropriate. The acid is not particularly limited, but examples thereof include sulfuric acid, hydrochloric acid, nitric acid, and acetic acid. The base is not particularly limited, but examples thereof include caustic soda, caustic potassium, lithium hydroxide, calcium hydroxide, barium hydroxide, sodium carbonate, and sodium bicarbonate.

[0032] When the acid or base is added, the acid or base may be added directly or as an aqueous solution. When the acid or base is added as an aqueous solution, the concentration is not particularly limited, but may be, for example, 1 mol / L or more.

[0033] In order to maintain the reaction conditions at pH 8.5 to 10.0, it is preferable to add an aqueous caustic soda solution. As the aqueous caustic soda solution, for example, one in which solid sodium hydroxide is dissolved in water or one in which the concentration of an aqueous sodium hydroxide solution produced by salt electrolysis is adjusted can be used.

[0034] In the production of the magnesium-manganese-M element composite raw material, the method of adding and mixing an acid or a base to control the pH is not particularly limited, and may be, for example, performed continuously or intermittently.

[0035] The oxidizing agent is not particularly limited, but may be, for example, an oxygen gas or hydrogen peroxide solution. The oxygen gas is not particularly limited, but may be, for example, air, oxygen, etc. From an economical viewpoint, air is most preferable. Gases such as air and oxygen are added by bubbling using a bubbler or the like. Meanwhile, hydrogen peroxide solution can be mixed in the same manner as metal salt aqueous solution and caustic soda aqueous solution.

[0036] The temperature at which the oxidizing agent is added to the aqueous solution containing the magnesium salt compound, the manganese salt compound, and the compound of the M element is not particularly limited, but is usually preferably 40° C. or higher.

[0037] The production of the magnesium-manganese-M element composite raw material does not require any particular atmospheric control, and can be carried out in normal air.

[0038] The magnesium-manganese-M element composite raw material can be produced by either a batch method or a continuous method. In the case of a batch method, the mixing time is optional. For example, it can be 3 to 48 hours.

[0039] The magnesium-manganese-M element composite raw material precipitated in the production of the magnesium-manganese-M element composite raw material can be isolated by an operation such as filtration, and it is preferable to further wash and dry the resulting mixture for ease of handling.

[0040] By washing, impurities attached or adsorbed to the magnesium-manganese-M element composite raw material can be removed. The washing method is not particularly limited, but an example thereof is a method in which the magnesium-manganese-M element composite raw material is added to water (e.g., pure water, tap water, river water, etc.) and the impurities are dissolved in the water.

[0041] The moisture content of the magnesium-manganese-M element composite raw material can be removed by drying. The drying method is not particularly limited, but may be, for example, drying the magnesium-manganese-M element composite raw material by heating at 110 to 150° C. for 2 to 15 hours.

[0042] In producing the magnesium-manganese-M element composite raw material, the raw material may be washed, dried, and then crushed.

[0043] In the pulverization, a powder having an average particle size suitable for the application is obtained. The pulverization conditions are arbitrary as long as the desired average particle size is obtained, and examples of the pulverization include wet pulverization and dry pulverization.

[0044] The magnesium-manganese-M element composite raw material obtained by the above method can be used in the method for producing lithium manganese spinel oxide of the present invention.

[0045] Examples of the lithium raw material include lithium carbonate, lithium hydroxide, lithium nitrate, lithium chloride, lithium iodide, and lithium oxalate.

[0046] Examples of phosphoric acid raw materials include lithium phosphates such as Li3PO4 and LiPO3, sodium phosphates such as Na3PO4, NaH2PO4, and Na2HPO4, potassium phosphates such as K3PO4, KH2PO4, and K2HPO4, magnesium phosphates such as Mg3(PO4)2, MgHPO4, and Mg(H2PO4)2, and ammonium phosphates such as NH4H2PO4 and (NH4)2HPO4.

[0047] Examples of the method for mixing the magnesium-manganese-M element composite raw material, the lithium raw material, and the phosphoric acid raw material include dry mixing, wet mixing, etc. In the case of wet mixing, a method in which the phosphoric acid raw material is dissolved in a solvent such as water or ethanol, and added to the magnesium-manganese-M element composite raw material and the lithium raw material is exemplified.

[0048] The calcination for obtaining the spinel-type lithium manganate of the present invention is carried out in air or in a high-concentration oxygen atmosphere (including a pure oxygen atmosphere), i.e., in an oxygen atmosphere with an oxygen content of 18 to 100 vol%, at 830°C to 960°C. At temperatures lower than 830°C, the BET specific surface area of ​​the spinel-type lithium manganate tends to increase, and at temperatures exceeding 960°C, the oxygen deficiency of the spinel-type lithium manganate increases, and as a result, the charge-discharge cycle characteristics tend to decrease when used as a positive electrode active material for a lithium secondary battery. The calcination is preferably carried out at 850°C to 950°C, more preferably at 900°C to 950°C.

[0049] Since the secondary particles of spinel-type lithium manganate tend to agglomerate during firing, the material is crushed to obtain the desired particle size. The crushing method is preferably by shear force to suppress the generation of fine powder and the increase in the BET specific surface area.

[0050] After crushing spinel-type lithium manganate, it is preferable to pass it through a sieve in order to remove coarse particles exceeding the thickness of the positive electrode. The mesh size of the sieve is preferably 100 μm or less, more preferably 50 μm or less.

[0051] By using the spinel-type lithium manganate of the present invention for the positive electrode of a lithium secondary battery, it becomes possible to construct a lithium secondary battery having excellent charge-discharge cycle characteristics and output characteristics at high temperatures, which could not be obtained conventionally.

[0052] The configuration of the lithium secondary battery other than the positive electrode is not particularly limited. As the negative electrode, materials that occlude and release Li, such as carbon-based materials, tin oxide-based materials, Li4Ti5O 12 , SiO, materials that form an alloy with Li, etc. are exemplified. Examples of materials that form an alloy with Li include silicon-based materials and aluminum-based materials. Examples of the electrolyte include organic electrolytes in which Li salts and various additives are dissolved in an organic solvent, Li-ion conductive solid electrolytes, and combinations thereof.

Examples

[0053] Next, the present invention will be described with specific examples, but the present invention is not construed as being limited to these examples.

[0054] <Measurement of Hausner ratio> The density (bulk density) in the non-tapped state immediately after filling the spinel-type lithium manganate obtained in the examples and comparative examples into a graduated cylinder, and the density (tapped density) after tapping 200 times were measured.

[0055] Based on the measured bulk density and tapped density, the Hausner ratio was determined according to the following formula.

[0056] Hausner ratio = tapped density / bulk density <Battery performance test> The spinel-type lithium manganese oxide obtained in each Example was mixed with a conductive binder (product name: TAB-2, manufactured by Hosen) in a weight ratio of 1 / 2 using an agate mortar. The resulting mixture was applied to a SUS mesh (SUS316) with a diameter of 16 mm at a rate of 2 ton / cm. 2 The mixture was uniaxially pressed at 80° C. to form a disk-shaped pellet, which was then dried under reduced pressure at 150° C. for 2 hours to form a positive electrode.

[0057] The negative electrode was a spherulitic graphite sheet (Hosen TSG-A1, nominal capacity 1.6 mAh / cm 2 ) was punched to a diameter of 16.156 mm and then subjected to a pressure of 3 ton / cm 2 The amount of the positive electrode active material was adjusted so that the negative electrode / positive electrode capacity ratio was 1.2.

[0058] LiPF6 is added at 1 mol / dm in a solvent of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:2. 3 The dissolved material was used as the electrolyte, a polyethylene sheet (product name: Celgard, manufactured by Polypore) was used as the separator, and a battery was fabricated using a CR2032 coin cell as the cell.

[0059] Using the fabricated battery, the current density was 0.14 mA / cm at a cell voltage between 4.25 V and 3.0 V at 24°C. 2 The battery was then subjected to one cycle of constant current / constant voltage charge / constant current discharge at 24°C, with the cell voltage between 4.25 V and 3.0 V, and a current density of 0.28 mA / cm 2 One cycle of constant current / constant voltage charge / constant current discharge was performed at 60°C, with the cell voltage between 4.25V and 3.0V, and the discharge capacity was taken as the battery capacity. Next, 50 cycles of constant current / constant voltage charge / constant current discharge were performed at a current density of 1-hour discharge rate for the battery capacity at 60°C, with the cell voltage between 4.25V and 3.0V, and the carbon counter electrode charge / discharge cycle characteristics were calculated from the ratio of the discharge capacity at the 50th cycle to the 1st cycle. The constant voltage charge was terminated when the charge current was attenuated to 1 / 10 of that at the constant voltage charge.

[0060] <Composition analysis, SO4 content, Na content measurement> The composition, SO4 content, and Na content of the lithium manganese spinel obtained in the examples and comparative examples were analyzed using an inductively coupled plasma atomic emission spectrometer (trade name: ICP-AES, manufactured by PerkinElmer Japan) after dissolving the lithium manganese spinel in an aqueous hydrochloric acid-hydrogen peroxide mixed solution.

[0061] <Measurement of BET Specific Surface Area> 1.0 g of the sample was placed in a glass cell for BET specific surface area measurement, and dehydration treatment was performed at 150 °C for 30 minutes under a nitrogen stream to remove the moisture adhering to the powder particles.

[0062] The treated sample was measured for BET specific surface area by the one-point method using a BET measuring device (trade name: MICROMERITICS DeSorbIII, manufactured by Shimadzu Corporation) with a mixed gas of 30% nitrogen - 70% helium as the adsorption gas.

[0063] <Measurement of Full Width at Half Maximum by XRD> Regarding the lithium manganese spinel obtained in the examples and comparative examples, the measurement of the full width at half maximum by XRD was performed using a powder XRD measuring device (trade name: Ultima IV, manufactured by Rigaku). The measurement conditions were as follows.

[0064] · Target: Cu · Output: 1.6 kW (40 mA - 40 kV) · Filter: Kβ filter · Divergence slit: 1° · Divergence vertical limit slit: 10 mm · Scattering slit: Open · Receiving slit; Open · Scanning mode: Continuous · Scan speed: 4.000° / min · Sampling width: 0.04° (2θ / θ) · Integration times: 1 time · Measurement range: 10 - 90° (2θ / θ) The XRD data of the obtained spinel-type lithium manganate was analyzed using analysis software (PDXL2) attached to the powder X-ray diffraction measurement device, and the integral width of the (400) plane near 2θ=44° was obtained.

[0065] In addition, to correct errors in the measurement device, a standard material for XRD (α-type quartz powder manufactured by NIST) was measured in advance, and the integral width of the standard material was subtracted from the integral width of the spinel-type lithium manganese oxide to obtain the half-width.

[0066] Example 1 Magnesium sulfate, aluminum sulfate, and manganese sulfate were dissolved in pure water to obtain an aqueous solution (metal salt aqueous solution) containing 0.15 mol / L (liter) magnesium sulfate, 0.03 mol / L aluminum sulfate, and 2.0 mol / L manganese sulfate. In addition, 8 L of pure water was placed in a reaction vessel with an internal volume of 10 L, and the temperature was raised to 60°C and maintained at that temperature.

[0067] The obtained metal salt aqueous solution was continuously fed to the reaction vessel at a feed rate of 12 g / min. In addition, air was bubbled into the reaction vessel as an oxidizing agent at a feed rate of 0.5 L / min. Furthermore, when the metal salt aqueous solution and air were fed, the reaction was continuously carried out while continuously adding a 5 mol / L aqueous sodium hydroxide solution (aqueous caustic soda solution) so that the pH was 8.7 (the redox potential during the reaction was 0.08 V). The reaction caused the magnesium-manganese-aluminum composite raw material to precipitate in the reaction vessel, and a slurry was obtained. The slurry in the reaction vessel was filtered and washed with pure water to obtain a wet cake. The wet cake was dried at 110° C. for 15 hours to obtain a magnesium-manganese-aluminum composite raw material.

[0068] A solution of 20.07 g of Mg(H2PO4) dissolved in 2 g of pure water was added to 20 g of the obtained magnesium-manganese-aluminum composite raw material, and 3 g of the obtained material was mixed with 0.8 g of lithium carbonate, and the mixture was fired at 930°C for 6 hours while circulating air at a rate of 5 L / min in a box furnace, and cooled to room temperature. The temperature increase rate was 100°C / hr, and the temperature decrease rate was 20°C / hr from 850°C to 600°C, and 100°C / hr from 600°C to room temperature. The obtained phosphate-containing spinel-type lithium manganate was crushed with a powerful small crusher (trade name: Force Mill, manufactured by Osaka Chemical Co., Ltd.), and then passed through a sieve with an opening of 32 μm to obtain phosphate-containing spinel-type lithium manganate.

[0069] The composition of the obtained phosphate-containing spinel-type lithium manganese oxide was Li 1.04 Mn 1.85 Mg 0.09 Al 0.02 O4. XRD measurement also showed that the obtained phosphate-containing spinel-type lithium manganese oxide was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). The phosphorus / manganese molar ratio, Hausner ratio, BET specific surface area, average particle size of lithium manganese oxide secondary particles, and the half-width of the (400) plane measured by XRD (hereinafter referred to as the measurement results) are shown in Table 1, and the battery performance is shown in Table 2.

[0070] [Table 1]

[0071] [Table 2]

[0072] Example 2 A phosphate-containing lithium manganese spinel-type manganate was obtained in the same manner as in Example 1, except that a magnesium-manganese-aluminum composite oxide obtained from a metal salt aqueous solution containing 0.08 mol / L (liter) magnesium sulfate, 0.03 mol / L aluminum sulfate, and 2.0 mol / L manganese sulfate was used, and the firing temperature was changed to 950° C.

[0073] The composition of the obtained phosphate-containing spinel-type lithium manganese oxide was Li 1.05 Mn 1.85 Mg 0.08 Al 0.02 O4. XRD measurement showed that the obtained phosphate-containing spinel-type lithium manganese oxide was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). The measurement results are shown in Table 1, and the battery performance is shown in Table 2.

[0074] Example 3 A phosphate-containing spinel-type lithium manganate was obtained in the same manner as in Example 1, except that a magnesium-manganese-aluminum composite oxide obtained from a metal salt aqueous solution containing 0.05 mol / L (liter) magnesium sulfate, 0.05 mol / L aluminum sulfate, and 2.0 mol / L manganese sulfate was used, and that the amount of Mg(H2PO4)2 was changed from 0.07 g to 0.035 g.

[0075] The composition of the obtained phosphate-containing spinel-type lithium manganese oxide was Li 1.03 Mn 1.85 Mg 0.05 Al 0.05 O4. XRD measurement showed that the obtained phosphate-containing spinel-type lithium manganese oxide was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). The measurement results are shown in Table 1, and the battery performance is shown in Table 2.

[0076] Example 4 A phosphate-containing lithium manganese spinel-type manganate was obtained in the same manner as in Example 1, except that a magnesium-manganese-nickel composite oxide obtained from a metal salt aqueous solution containing 0.08 mol / L (liter) magnesium sulfate, 0.03 mol / L nickel sulfate, and 2.0 mol / L manganese sulfate was used, and the firing temperature was changed to 900° C.

[0077] The composition of the obtained phosphate-containing spinel-type lithium manganese oxide was Li 1.04 Mn 1.86 Mg 0.08 Ni 0.02 O4. XRD measurement showed that the obtained phosphate-containing spinel-type lithium manganese oxide was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). The measurement results are shown in Table 1, and the battery performance is shown in Table 2.

[0078] Example 5 A phosphate-containing lithium manganese spinel-type oxide was obtained in the same manner as in Example 1, except that a magnesium-manganese-cobalt composite oxide obtained from a metal salt aqueous solution containing 0.08 mol / L (liter) magnesium sulfate, 0.03 mol / L cobalt sulfate, and 2.0 mol / L manganese sulfate was used, and the firing temperature was changed to 900° C.

[0079] The composition of the obtained phosphate-containing spinel-type lithium manganese oxide was Li 1.05 Mn 1.85 Mg 0.08 Co 0.02 O4. XRD measurement showed that the obtained phosphate-containing spinel-type lithium manganese oxide was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). The measurement results are shown in Table 1, and the battery performance is shown in Table 2.

[0080] Comparative Example 1 Manganese sulfate was dissolved in pure water to obtain a 2.0 mol / L aqueous manganese sulfate solution. After 8 L of pure water was placed in a reaction vessel having an internal volume of 10 L, the temperature was raised to 60° C. and maintained at that temperature.

[0081] The obtained manganese sulfate aqueous solution was continuously fed to the reaction vessel at a feed rate of 12 g / min. In addition, air was bubbled into the reaction vessel as an oxidizing agent at a feed rate of 0.5 L / min. Furthermore, when the manganese sulfate aqueous solution and air were fed, the reaction was continuously carried out while continuously adding 5 mol / L of sodium hydroxide aqueous solution (caustic soda aqueous solution) so that the pH was 7.5 (the redox potential during the reaction was 0.08 V). As a result of the reaction, Mn3O4 was precipitated in the reaction vessel, and a slurry was obtained. The slurry in the reaction vessel was filtered and washed with pure water to obtain a wet cake. The wet cake was dried at 110°C for 15 hours to obtain Mn3O4.

[0082] After 3 g of Mn3O4, 0.8 g of Li2CO3, and 0.12 g of Mg(OH)2 (manufactured by Wako Pure Chemical Industries, Ltd., average particle size 0.07 μm) were mixed in a dry state, the mixture was sintered, crushed, and classified in the same manner as in Example 1. The composition of the obtained spinel-type lithium manganate was Li 1.04 Mn 1.86 Mg 0.10 The XRD measurement showed that the obtained spinel-type lithium manganese oxide was a single phase of JCPDS No. 35-782 (LiMn2O4). The measurement results are shown in Table 1, and the battery performance is shown in Table 2. It is clear from Table 2 that the carbon counter electrode cycle characteristics of Comparative Example 1 are inferior to those of the Examples. [Industrial Applicability]

[0083] The spinel-type lithium manganese oxide of the present invention has Mg atoms and M elements uniformly dispersed therein and has a specific Hausner ratio, BET specific surface area, and secondary particle size. Therefore, the spinel-type lithium manganese oxide has excellent charge-discharge characteristics at high temperatures, in particular, carbon counter electrode charge-discharge characteristics, and can be used as a positive electrode active material for a lithium secondary battery having excellent output characteristics.

Claims

1. Contains phosphate and has the chemical formula Li 1+X Mn 2-X-Y-Z Mg Y M Z O 4 (wherein M is at least one element selected from Al, Ca, Ti, V, Cr, Co and Ni, and 0.02≦X≦0.10, 0.05≦Y≦0.30, and 0≦Z≦0.30), characterized in that the spinel-type lithium manganate has a Hausner ratio, which is expressed as the ratio of tap density to bulk density, of 1.85 or less.

2. 2. The spinel-type lithium manganate according to claim 1, wherein the phosphorus / manganese molar ratio is 0.0015 or more and 0.1 or less.

3. BET specific surface area is 0.2m 2 / g or more 1.5m 2 3. The spinel-type lithium manganate according to claim 1, wherein the lithium manganese oxide has a molecular weight of 1.0 to 1.0 g / g or less.

4. 4. The spinel-type lithium manganate according to claim 1, wherein the average particle size of the secondary particles is 4 μm or more and 20 μm or less.

5. 5. The spinel-type lithium manganate according to claim 1, wherein the half-value width of the (400) plane as measured by XRD is 0.005 to 0.

08.

6. SO 4 The spinel-type lithium manganese oxide according to any one of claims 1 to 5, characterized in that the content of is 0.3 wt % or more and 1.0 wt % or less.

7. 7. The spinel-type lithium manganate according to claim 1, wherein the Na content is 3,000 wtppm or less.

8. The method for producing spinel-type lithium manganate according to any one of claims 1 to 7, characterized in that a magnesium-manganese-M element composite raw material (M is at least one element selected from Al, Ca, Ti, V, Cr, Co, and Ni), a lithium raw material, and a phosphoric acid raw material are mixed, and the mixture is fired at 830°C to 960°C in air or in a high-concentration oxygen atmosphere (including a pure oxygen atmosphere), and then crushed.

9. An electrode comprising the spinel-type lithium manganese oxide according to any one of claims 1 to 7.

10. A lithium secondary battery using the electrode according to claim 9 as a positive electrode.

Citation Information

Patent Citations

  • Latch mechanism for spreader

    JP1980056983A

  • Lithium-ion secondary battery

    JP2006156317A

  • Lithium metal composite oxide and method for producing the same

    JP2013112531A

  • Mixed cathode materials

    JP2014524133A

  • Lithium manganese composite oxide powder and production method therefor

    JP2017031006A